High-sensitivity real-splitting anti-PT-symmetric microscale optical gyroscope - De Carlo, Martino; De Leonardis, Francesco; Lamberti, Luciano; Passaro, Vittorio M N (Optics letters, 2019)
Optical gyroscopes measure the angular velocity using the Sagnac effect. However, the resonance splitting due to the Sagnac effect is directly proportional to the linear dimensions of the device. Consequently, integrated optical gyroscopes are still the subject of research. We propose the idea and the design of an anti-parity-time (APT)-symmetric optical gyroscope exhibiting a resonance splitting independent from the dimensions of the device. With a 80  μm×40  μm footprint integrated device, we demonstrated that it is possible to achieve a resonance splitting 10 times higher than the one obtained through the classical Sagnac effect. With respect to the previously proposed parity-time (PT)-symmetric gyroscope, our solution exhibits a real frequency splitting, directly measurable at the output power spectrum. Moreover, it can be kept at its exceptional point more accurately than the PT-symmetric counterpart. Finally, the anti-PT-symmetric gyroscope presented here can detect the sign of the angular velocity differently from the PT-symmetric one.